WHAT THE «KAZAKHSTAN TRUTH» NEWSPAPER TELLS ABOUT COVID-19 - Skripnikova, A. I.; Ndiaye, I. A. (Farabi Journal of Social Sciences, 2021)
Mass media around the world have actively covered the situation with coronavirus. The current outbreak of infection has been much more famed in media than previous epidemics, like SARS or Ebola. Kazakhstan is no exception. The purpose of this article is to analyze journalistic texts on the coronavirus and tried to highlight existing trends, identify errors and give a description of the overall picture of the stream of publications using the example of country’s main newspaper. The scientific significance of the work lies in the fact that earlier similar studies on the topic have not been conducted. In terms of methodology, the content analysis was chosen as the main research method. All published articles were broken into several sectors manually. The data was summarized. Having preliminary sorted all the information, further manually work was carried out to calculate the necessary quantitative data. The value of the work lies in the data obtained during the process of work. The following main results were received: on average, the periodical publishes almost two articles about coronavirus per day; foreign news portals prevail as sources of information; among the genres informational notes and reports from press conferences prevail, and there are no author’s interviews or journalistic investigations; vast majority of photographic materials newspaper borrows from Internet, illustrative photographs prevail; most of the journalists in their articles refer to officials and are not looking for independent experts; there is the limit of information and it is simply copied from article to article; the editorial office seeks to maintain neutrality – there is no material that would have a racist, offensive (in relation to the country or infected people) character. All findings were divided into positive and negative. To overcome negative aspects some recommendations were made. This is the main practical significance of the work’s results. Key words: Kazakhstan, mass media, coronavirus, The «Kazakhstan Truth», copyright materials